Modeling the microstructure at steel–concrete interface in reinforced concrete. (14th November 2019) - Chen, Fangjie; Baji, Hassan; Li, Chun‐Qing; Lau, Ian; Ma, Baoguo
Abstract: The microstructure at the steel–concrete interface can significantly affect corrosion of steel and corrosion‐induced cracking of reinforced concrete (RC). This paper aims to model the thickness of porous band around the steel–concrete interface as a function of concrete design parameters. Both the maximum ( d 0, max ) and equivalent uniform thickness ( d ¯ 0 ) of the porous band are thoroughly examined. The developed model is robust in predicting the thickness around the steel–concrete interface, the maximum and equivalent uniform thickness of the porous band. It is found in the paper that water to cement ratio and concrete cover show strong correlations with the porous band ( d 0 ) while aggregate size shows no correlation. The contribution of the paper is that the developed models for porous band around the steel–concrete interface can improve the prediction of corrosion‐induced cracking of RC and hence prevent premature and avoidable failures of corrosion affected concrete structures.